(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2025)
This study aims to determine the effect of the number of visitors to the Ujung Tamiang ecotourism object in Kuala Pusung Kapal Village, Seruway District, Aceh Tamiang Regency. Ecotourism is a tourism activity that is oriented towards nature, with the motivation of visits to refresh, educate and build interest in caring for conservation. This study was conducted in Aceh Tamiang Regency. The sampling technique used Accidental Sampling with the number of research respondents as many as 30 respondents visiting the Ujung Tamiang ecotourism. The data used in this study are primary data and secondary data. The data analysis method used is multiple linear regression, using the Classical Assumption Test (Normality Test, Multicollinearity, and Heteroscedasticity) and Hypothesis Test (F Test, t Test, and R2). The results of the study showed that simultaneously there was an influence of independent variables (Travel Cost, Travel Time, Distance and Attraction Objects) on the dependent (number of visitors). Partially, the factors Travel Cost X1, Travel Time X2, Distance X3 did not have a significant effect on the number of visitors. Meanwhile, the tourist attraction object X4 has a significant influence on the number of visitors to the Ujung Tamiang ecotourism object in Kuala Pusung Kapal Village, Seruway District, Aceh Tamiang Regency. Indonesia.